(untitled) (Research, Society and Development, 2022)
Endodontics is constantly evolving, developing new materials frequently. In addition to providing an adequate apico-coronal sealing, the filling cements must present close to ideal physical, chemical and biological characteristics, with biological characteristics determining the safety of the cement to be used. The biocompatibility characteristics are the subject of several studies in the literature, however, there are few studies that evaluate the carcinogenicity of these materials. Thus, it is necessary to evaluate this aspect since, when in contact with the root canal, the cement reaches adjacent structures of the dental element. This work aimed to evaluate the carcinogenic potential of the bioceramic cement Bio-C Sealer using as an experimental model the test for detection of epithelial tumors in Drosophila melanogaster. For this, doxorubicin was used as a positive control and ultrapure water as a negative control. The flies were exposed to 4 different cement concentrations: 1:50; 1:100; 1:200 and 1:400 and tumor frequency count results were compared to positive and negative control values. There was an increase in the frequency of tumors at all concentrations in relation to the negative control; in addition, the regression test showed that the 1:50 concentration increased the frequency of individuals with tumors, being statistically similar to the positive control group. The results obtained allow us to conclude that the endodontic cement Bio-C Sealer presented an increase in the tumor frequency rate with dose-dependent behavior.